PENGARUH PEMBERIAN KOMPRES HANGAT (JAHE) TERHADAP SKALA NYERI SENDI PASIEN ARTRITIS RHEUMATOID - Virda Yuniarti, Enny; Kharisma, Ani (JURNAL KEPERAWATAN BINA SEHAT, 2015)
One of the non pharmacological intervention can be done independently of the nursein lowering the scale of pain with rheumatoid arthritis do warm ginger compresses on patient to lower arthritis rheumatoid pain scale. The purpose of this research was to analyze the effect of granting a warm compress ginger against the scale of the joint pain of rheumatoid arthritis patients.. The research design are eskperiment with one group pre test post test design. Population of this research are all of rheumatoid arthritis sufferes as much as 25 respondents and sample taken with total sampling techniques. Data taken by observation sheet pain bourbonais instrument. The results showed there is influence the awarding of a warm compres ginger against the scale of the scale of the joint pain of rheumatoid ar arthritis patients in the village of Bleberan sub-district of Jatirejo Mojokerto as evidenced by the result of a test of Wilcoxon ρ = 0.001, α =0.05 so ρ <α so that H1 accepted. The principle of non pharmacological pain management on a warm compres ginger focus on stretching musles utilizing heat energy and efficacy of ginger it self, so that from inside the body can produce homrones such as serotonin and endorphin relaxan so that it can reduce pain.Key Words: Warm Compress, Arthritis Rhematoid¸ Joint Pain